EKSISTENSI GRASI MENURUT PERSPEKTIF HUKUM PIDANA - Chaerul Risal (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2017)
Pardon is a form of amnesty in the form of change, mitigation, abolition or elimination of criminal practice to the convict provided by the President. The powers of the President grant pardons related to criminal law in a subjective sense. The subjective criminal law discusses the right of the state to impose and execute the criminal. The right of such a state is a great state right, so it is necessary to find the basis of its foothold through the theory of punishment. The President in granting pardons should be based on the theory of punishment.Keywords: Grasi, Authority of the President Grasi merupakan suatu bentuk pengampunan berupa perubahan, peringanan, pengurangan, atau penghapusan pelaksanaan pidana kepada terpidana yang diberikan oleh Presiden. Kewenangan Presiden memberikan grasi terkait dengan hukum pidana dalam arti subyektif. Hukum pidana subyektif membahas mengenai hak negara untuk menjatuhkan dan menjalankan pidana. Hak negara yang demikian ini merupakan hak negara yang besar, sehingga perlu dicari dasar pijakannya melalui teori pemidanaan. Presiden dalam memberikan grasi harus didasarkan pada teori pemidanaan.Kata kunci : Grasi, Kewenangan Presiden